Penerapan Evidence Based Practice Mind-Body Therapy (Mindfullness Based Stress Reduction) dalam Menurunkan Ansietas pada Pasien Coronaryheart Disease (CHD) - Nurrahman, Aris; Jumaiyah, Wati; Yunitri, Ninik; Agung, Rizki Nugraha (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Coronary Heart Disease (CHD) is a health condition that is not caused by infectious factors and is a serious concern in society, with the number of cases continuing to increase both globally and in Indonesia. Someone who experiences stress in a CHD condition tends to experience various symptoms such as anxiety, disappointment, difficulty feeling calm after experiencing irritation, and is susceptible to feeling angry or offended by small things. People with CHD who experience stress also need a longer time to feel relaxed or calm again, the impact is very detrimental to heart health. From a behavioral perspective, high levels of stress hormones also make individuals with CHD experience difficulty sleeping. This study aims to apply Evidence-Based Nursing Practice (PKBB) to understand the impact of applying Mind-body Therapy on anxiety levels in CHD patients. Use descriptive tests for continuous variables such as age, while binomial tests are used for nominal and ordinal variables such as gender and education level. To calculate the number of respondents, researchers used G*Power Version 3.1 software. In G*Power, researchers use family tests: t-test, statistical tests: the average difference between two dependent means (matched pairs), type of power analysis: a priori, calculating the required sample size - keeping in mind alpha, power, and effect size, with two-tailed input parameters, total effect size of 0.78, alpha error probability of 0.05, and power of 0.80. The results showed 15 respondents. Mind-body therapy has been proven to be successful in reducing anxiety levels in CHD patients. Mind-Body Therapy is carried out for 8 weeks, 6 times a week, with a duration of 30 minutes in a quiet environment. Keywords: Evidence Based Practice Mind-Body Therapy, Mindfullness Based Stress Reduction, Ansietas, Coronary Heart Disease (CHD).  ABSTRAK Penyakit Jantung Koroner (PJK) merupakan suatu kondisi kesehatan yang bukan disebabkan oleh faktor penularan dan menjadi perhatian serius dalam masyarakat, dengan jumlah kasus yang terus meningkat baik secara global maupun di Indonesia. Seseorang yang mengalami stres dalam kondisi PJK cenderung mengalami berbagai gejala seperti kecemasan, kekecewaan, sulit merasa tenang setelah mengalami kekesalan, serta rentan terhadap perasaan marah atau tersinggung oleh hal-hal kecil. Orang dengan PJK yang mengalami stres juga memerlukan waktu yang lebih lama untuk dapat kembali merasa rileks atau tenang, dampaknya sangat merugikan bagi kesehatan jantung. Dari segi perilaku, tingginya hormon stres juga membuat individu dengan PJK mengalami kesulitan dalam tidur. Penelitian ini bertujuan menerapkan Praktik Keperawatan Berbasis Bukti (PKBB) guna memahami dampak penerapan Terapi Mind-body terhadap tingkat kecemasan pada pasien PJK.  Menggunakan uji deskriptif untuk variabel kontinu seperti usia, sementara uji binomial digunakan untuk variabel nominal dan ordinal seperti jenis kelamin dan tingkat pendidikan. Untuk menghitung jumlah responden, peneliti memanfaatkan perangkat lunak G*Power Versi 3.1. Pada G*Power, peneliti menggunakan uji keluarga: t-test, uji statistik: perbedaan rata-rata antara dua rata-rata tergantung (matched pairs), jenis analisis daya: a priori, menghitung ukuran sampel yang diperlukan - dengan mengingat alpha, daya, dan ukuran efek, dengan parameter input berupa dua ekor, ukuran efek total 0,78, alpha error probabilitas 0,05, dan daya 0,80. Hasilnya menunjukkan 15 responden. Terapi Mind-body terbukti berhasil mengurangi tingkat kecemasan pada pasien PJK. Pelaksanaan Terapi Mind-Body dilakukan selama 8 minggu, 6 kali seminggu, dengan durasi 30 menit di lingkungan yang hening. Kata Kunci: Praktek Berbasis Bukti Terapi Pikiran-Tubuh, Pengurangan Stres Berbasis Perhatian, Ansietas, Penyakit Jantung Koroner (PJK).